2020
DOI: 10.1038/s41522-020-0130-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial predictors of healing and short-term effect of debridement on the microbiome of chronic wounds

Abstract: Chronic wounds represent a large and growing disease burden. Infection and biofilm formation are two of the leading impediments of wound healing, suggesting an important role for the microbiome of these wounds. Debridement is a common and effective treatment for chronic wounds. We analyzed the bacterial content of the wound surface from 20 outpatients with chronic wounds before and immediately after debridement, as well as healthy skin. Given the large variation observed among different wounds, we introduce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 50 publications
3
83
1
2
Order By: Relevance
“…However, neither patient demographics nor wound type influenced the bacterial composition of the chronic wound microbiome [ 17 ]. Different studies have described this DFU microbiota [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Although they have produced interesting results and confirmed that the microbiota is a highly dynamic microbial community that maintains a relationship with the host, understanding the complex competitive or synergistic interaction between commensal and pathogenic microorganisms is necessary as it could play an important role in the severity and evolution of the wound.…”
Section: Pathophysiology Of Diabetic Foot Ulcersmentioning
confidence: 99%
“…However, neither patient demographics nor wound type influenced the bacterial composition of the chronic wound microbiome [ 17 ]. Different studies have described this DFU microbiota [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Although they have produced interesting results and confirmed that the microbiota is a highly dynamic microbial community that maintains a relationship with the host, understanding the complex competitive or synergistic interaction between commensal and pathogenic microorganisms is necessary as it could play an important role in the severity and evolution of the wound.…”
Section: Pathophysiology Of Diabetic Foot Ulcersmentioning
confidence: 99%
“…The interruption in the healing process may occur for a number of reasons connected to one’s lifestyle and health condition. For example, smoking, malnutrition, obesity, low mobility, neuropathy, diabetes, vascular diseases and skin disorders have been linked to the increasing chronicity of wounds, where healing has not been achieved within 3–6 weeks [ 2 , 3 , 4 ].…”
Section: Wound Healing and Electrospun Wound Dressingsmentioning
confidence: 99%
“…The leading causes of non-healing chronic wounds are infection, pathological inflammation and formation of biofilms [ 2 , 6 ]. Therefore, wound care usually comprises of debridement followed by antimicrobial treatment and application of wound dressings.…”
Section: Wound Healing and Electrospun Wound Dressingsmentioning
confidence: 99%
“…Moreover, results from MacDonald et al [ 45 ] suggested that healing DFUs had a higher abundance of Actinomycetales and Staphylococcaceae , while non-healing DFUs showed higher abundances of Bacteroidales and Streptococcaceae . Facultative anaerobes, especially of the genus Enterobacter , were found to be significantly associated with lack of healing, and thus a negative prognostic factor derived from knowing the chronic wound microbiome [ 46 ]. However, despite these trends, no statistically significant correlation was found between wound status (healed versus unhealed) and the abundance of any particular taxa at the species or genus level in several other studies [ 29 , 43 , 47 ].…”
Section: The Dynamic Dfu Microbiomementioning
confidence: 99%
“…Wound debridement and wound dressings have also been shown to significantly modify the wound microbiome in DFU patients, with evidence that this led to favorable outcomes [ 34 ], even for long-term chronic wounds [ 43 ]. However, Verbanic et al [ 46 ] found no difference in the wound microbiome between pre-debridement and 1–2 min post-debridement specimens, suggesting that debridement did not alter the wound microbiome directly in the short term. Notably, in this study, the extent and depth of debridement, as well as the type of instrument used (curette, scalpel, scissors, or tissue nipper), were not standardized and were determined by the treating physician.…”
Section: Effect Of Medical Intervention On the Dfu Microbiomementioning
confidence: 99%